Chapter La rielaborazione dei mitemi orfici in Microcosmi. Tra vulgata classica e favola indiana - Fallani, Andrea (Biblioteca di Studi di Filologia Moderna, 2021)
Starting from the critics' observations about the structure of Microcosmi, the essay focuses on the key role played by the love story between the protagonist-narrator and his wife Marisa, a sort of rewriting of Orpheus and Eurydice's myth. Convergences and variations between the classic vulgate of the myth and the pseudo-rewriting of Microcosmi are highlighted. The essay also focuses on the Indian myth of Savitri and Sátiavan, to understand the source of the many substantial variations and, in particular, the reversal of roles between male and female characters. This myth turns out to be a privileged source for the rewritings of the Orpheus' myth that are offered by Magris in his Microcosmi.